Respostas

2014-05-21T00:22:12-03:00
F(x) = 3x +  \frac{8}{2}    podemos simplificar a equação: f(x) = 3*x + 4


substitua os valore de f(x) em x na equação.

f(3)= 3*x + 4    =>  f(3) = 3*3 + 4 = >  f(3) = 9 + 4 => f(3) = 13

f(-2) = 3*x + 4 => f(-2) = 3 * -2 + 4 => f(-2) = -6 + 4  => f(-2) = -2

f(1/4) = 3*x + 4 => f(1/4) = 3* 1/4 + 4 => f(1/4) =  \frac{3}{4} +4  =>  \frac{19}{4}

f(√2) = 3*x + 4 =>  f(√2) = 3 * √2 +4 =>  pode ser assim também => f(√2) = 4+3*√2

ou f(√2) = 3 * √2 + 4   => f(√2) = 4,24 + 4 => f(√2) = 8,24